Higher-Order Spreadsheets with Spilled Arrays - Williams, Jack; Joharizadeh, Nima; Gordon, Andy; Sarkar, Advait (European Symposium on Programming, 2020)
We develop a theory for two recently-proposed spreadsheet mechanisms: gridlets allow for abstraction and reuse in spreadsheets, and build on spilled arrays, where an array value spills out of one cell into nearby cells. We present the first formal calculus of spreadsheets with spilled arrays. Since spilled arrays may collide, the semantics of spilling is an iterative process to determine which arrays spill successfully and which do not. Our first theorem is that this process converges deterministically. To model gridlets, we propose the grid calculus, a higher-order extension of our calculus of spilled arrays with primitives to treat spreadsheets as values. We define a semantics of gridlets as formulas in the grid calculus. Our second theorem shows the correctness of a remarkably direct encoding of the Abadi and Cardelli object calculus into the grid calculus. This result is the first rigorous analogy between spreadsheets and objects; it substantiates the intuition that gridlets are an object-oriented counterpart to functional programming extensions to spreadsheets, such as sheet-defined functions.